Inkjet‐Printed TiO2 Nanoparticles from Aqueous Solutions for Dye‐Sensitized Solar Cells (DSSCs). Issue 8 (29th June 2015) - Cherrington, Ruth; Hughes, Darren J.; Senthilarasu, S.; Goodship, Vannessa
Abstract This work reports on the formulation of suitable ink for inkjet printing of TiO2 by investigating the critical parameters of particle size, pH, viscosity, and stability. Aqueous suspensions of TiO2 nanoparticles (Degussa, P25) were prepared with the addition of 25 wt % polyethylene glycol 400 as a humectant to minimize drying at the printer nozzles and reduce the likelihood of nozzle blockage. The inkjet‐printed TiO2 layers were assembled into dye‐sensitized solar cells. The current–voltage (I–V) characteristics were measured under one sun (air mass 1.5, 100 mW cm−2) using a source meter (Model 2400, Keithley Instrument, Inc.), and the active area of the cell was 0.25 cm2. The inkjet‐printed TiO2 photoanode produced a device with a short‐circuit current (Isc) of 9.42 mA cm−2, an open‐circuit voltage (Voc) of 0.76 V, and a fill factor (FF) of 0.49, resulting in a power conversion efficiency (PCE) of 3.50 %.